(3OQI GdCSdGc aj OhdI GdCJQGcs - (3GdMSf Hf YeQ Hf GdMSf Hf MHjH, CHh eMeO, HOQ GdOjf GdMdHj,J (B779 (3g` s
(3ChdgG (B:s
(3jHJOC HSfI (B648 (3g` s
(3BNQgG (B:s
(3jfJgi Edi SfI (B714 (3g` ,HJQLeI CHh YHO Gddg GdehUdi s
(3fSNI KGfjI eUhQI Yf fSNI HGdCSJGfIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B208 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B206 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B169s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B37 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B129 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B737s
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeYI GdeUQjI (B(22961) s
Keywords: (3GdJGQjNs